Automated screening tool for Subcutaneous Implantable Defibrillator in Brugada syndrome has a high eligibility rate which is predicted by simple electrocardiographic parameters. (25th November 2020) - Marelli, S; Kukavica, D; Mazzanti, A; Chargeishvili, T; Trancuccio, A; Monteforte, N; Bloise, R; Marino, M; Napolitano, C; Priori, S.G
Abstract: Background: Manual electrocardiographic (ECG) screening tools for the use of subcutaneous cardiac defibrillator (S-ICD) have been associated with high ineligibility rates in Brugada syndrome patients (BrS). Although recent works identified ECG parameters for S-ICD eligibility in general population, automated screening tool (AST) for S-ICD eligibility have not even been assessed in large series of patients with BrS. Purpose: This study evaluates the AST-derived eligibility rates for an S-ICD in patients with BrS, and ECG parameters associated with S-ICD eligibility. Methods: Screening for S-ICD eligibility was performed using AST in 194 consecutive patients with BrS. Eligibility was defined when at least one of the three vectors was acceptable both in supine and standing position. Twelve-lead ECGs were registered during the screening. ECG parameters associated with AST eligibility were identified using multivariable logistical regression. Results: Our study population consisted of 194 patients, with male preponderance (n=165/194; 85%); and were 43±12 years old at the time of screening. Majority of patients presented a spontaneous type 1 pattern during screening (n=128/194; 66%), with an average pattern height of 3±3 mm. Remarkably, 93% of patients passed the screening with AST. No differences in eligibility rates in terms of gender (93% males vs. 93% females eligible; p=1) and age (48±9 years non-eligible vs. 42±12 eligible; p=0.07) existed. Notably, our eligibility rate was 2.5 times higher than rates reported in literature when using manual screening tools (p=0.023). Independent 12-lead ECG parameters (Table) associated with AST eligibility were duration of S wave <80 ms in aVF and R/T ratio ≥3 in lead II (Figure), which have a high positive predictive value (97% and 99%, respectively) for screening eligibility. Conclusions: Most BrS patients (93%) are eligible for S-ICD when AST is used. S wave <80 ms in aVF, and R/T ratio ≥3 in lead II have a high positive predictive value for S-ICD eligibility. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Italian Ministry of Research and University Dipartimenti di Eccellenza 2018–2022 grant to the Molecular Medicine Department (University of Pavia)